PENGARUH METODE PENCUCIAN PADA PEMBUATAN BIODIESEL DARI MINYA JARAK PAGAR - Muharto, Pramudita R.A , Adhy Ma, Mahfud, (Jurnal Teknik Kimia, 2009)
The aims of this study is to know the effect of washing method in quality of biodiesel obtained from Jatropha curcas oil through transesterification process and to find out the chemical and physical properties of biodiesel that appropriate with ASTM standard 6751. The operating variables are : washing methods (aeration, spray and agitation); time of washing (0; 0,5; 1; 2 hours) The experiment conducted in 1 liter round bottom flask equipped with waterbath and temperature controlled. Firstly, a certain quantity of Jatropha curcas oil, methanol, and KOH catalysts ared determined. Then, KOH catalyst is diluted into methanol and introduce to reactor containing 500 ml jathropa oil. The tempearture was fixed at 60oC and the agitaion 200 rpm. The reaction transesterification process held during 1 hour. The Product of reaction is cooled untill two layers are formed. Upper layer is methyl esther of fatty acid and lower layer is glycerol. After that, upper layer is separated from lower layer and wash with pure water according to the operating variabels. The methyl ester obtained is characterized to obtain some physical properties at PT Pertamina UPPS V Laboratory. The results shows that the methods of washing not significanly influence, but the time of washing have a sligtly effect in properties of Biodiesel.  Key words :Biodiesel, Washing, Jatropha curcas oil